Trends and Patterns in Organizational Resilience Research: A Bibliometric Analysis Using Scopus Database - Thike, Bandana Sigh; Shrestha, Sajeeb Kumar (Khwopa Journal, 2025)
As the world becomes increasingly dynamic, complex, uncertain, volatile, and ambiguous, the need to build more organizationally resilient entities has come to the fore; however, the body of knowledge on this topic is still slightly different. To bridge this gap, a bibliometric analysis was performed on 272 publications obtained from the Scopus database, and then with the help of VOS Viewer, the essential contributions, gaps, and trends were reviewed and mapped. The analysis further revealed key issues important to the understanding of organizational resilience, such as resilience, crisis management, innovation, dynamic capabilities, and change management. The results indicate the articles on organizational resilience published in Scopus between 2007 and 5th December 2024. In addition to mapping the field of organizational resilience research, the study recommends important areas for further investigation by offering a thorough overview of institutional affiliations, nations, authors, journals, publications, citations, co-citations, and keyword co-occurrences. By improving theoretical and practical knowledge of organizational resilience, this work helps professionals to create strong plans to deal with the difficulties of the dynamic world.